The New Encyclopaedia Britannica. (Chicago : Encyclopedia Britannica, inc., 1975)
The Encyclopaedia Britannica is published with editorial advice of the faculties of the University of Chicago;a committee of persons holding academic appointments at the universities of Oxford,Cabridge,London ,and Edinburgh; a committee at the University of Toronto;and committees withdrawn from members of the faculties of the University of Tokyo and the Australian National University.
The Micropaedia and Macropaedia are numbered v. 1-10 and v. 1-19, respectively.
Includes bibliographies and index.
Keywords: Encyclopedias and dictionaries